HUBUNGAN POWER OTOT LENGAN BAHU DAN KOORDINASI MATA DAN TANGAN DENGAN KETEPATAN SERVIS PADA SISWA EKSTRAKURIKULER BOLAVOLI SMP NEGERI 5 PEKANBARU - Rizaldo, Rizky; Ramadi, Ramadi; juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : Based on field observations, it is clear that during practice and inter-school matches,it is seen from the ball blow when the top serve of the ball is often out of the field and sometimes stells on the net or hit the net, some even do not get to the field opponent. In accordance with the background problem and problem formulation, this study aims to determine the relationship of muscle strength of the arms and shoulders and eye and hand coordination with the accuracy of service over the men’s bola voli team SMP Negeri 5 Pekanbaru. The population in this study is the men’s bola voli team SMP Negeri 5 Pekanbaru registered or active follow the training which amounted to 12 people. Because the sampling technique was purposive sampling, only men’s volleyball extracurricular team from SMP Negeri 5 Pekanbaru were taken in 12 people and without women’s volleyball extracurricular team. This research was carried out in volleyball field of SMP Negeri 5 Pekanbaru on February 6, 2018. Instrumen in this research a test service, test an explosive arm muscles using the Medicine ball, and Eye-hand Coordination test of [throw catch tennis balls]. The data obtained in the analysis by using design research correlation. Based on the results of research that has been authors described in the previous chapter, it can be concluded there is the relationship between power arm and shoulder muscles with the accuracy of to service on the men’s bola voli extracurricular SMP Negeri 5 Pekanbaru. There is a relationship that is not in the direction in the coordination of eye and hand with the service accuracy on the men’s bola voli extracurricular SMP Negeri 5 Pekanbaru. Then, there is a relationship of power arm and shoulder muscles and the coordination of eye and hand with the service accuracy.Key Words: Muscle Arm and Shoulder Strength, eye and Hand Coordination, Service Accuracy